Media event and Latin performance: Bad Bunny at Super Bowl LX and the symbolic reconfiguration of "America" (2026). - Pérez-Rufi, José Patricio (Universidad de Málaga, 2026)
This paper examines Bad Bunny’s (Benito Antonio Martínez Ocasio) televised halftime performance at Super Bowl LX, broadcast on 8 February 2026. Drawing on the theoretical framework of media events, media rituals and the culture of spectacle, it interprets the performance as a device of visibility and memory that reorganises the ritual of the major sporting event. The staging unfolds a symbolic grammar centred on Puerto Rico and the Latin diaspora: the opening amid sugarcane fields activates a colonial memory; the little house condenses home, community and cultural pride; the live wedding and the neighbourhood party advance a politics of affect; and the sequence focused on electrical infrastructure positions the island’s material precarity within the global public sphere. In its closing movement, the re-signification of the formula “God bless America”, through the enumeration of countries across the continent and the display of flags, constructs an inclusive pan-Americanism that challenges the appropriation of the term “America” as an exclusive synonym for the United States. The analysis argues that the spectacle offers a counter-narrative of citizenship: against contemporary discourses of fear, criminalisation and exclusion directed at Latin migration, Bad Bunny articulates recognition, self-esteem and continental fraternity without resorting to belligerent rhetoric.
Bad Bunny, the stage name of Benito Antonio Martínez Ocasio, ranks among the most influential cultural actors of the post-digital cycle, both for the sheer scale of his global consumption and for his ability to translate local experience into transnational pop idioms. His career forms part of the expansion of reggaetón and Latin trap as sonic industries that have reshaped hierarchies within the music market, displaced the geolinguistic axis of the mainstream, and established Spanish-language urban music as one of the commercial cores of contemporary audiovisual culture (Rivera et al., 2009; Wikström, 2020; Negus, 2019). Bad Bunny has advanced a notion of authorship that combines mass repertoire, aesthetic experimentation and control over his public image, in dialogue with a media ecology in which music circulates as visual archive, staged event and platform-based conversation (Jenkins, 2006; Couldry & Hepp, 2017). From Puerto Rico, a territory of ambiguous citizenship and enduring colonialism, he has turned Boricua identity into a symbolic centre capable of contesting external representations, and has linked that contestation to a communitarian ethic and an aesthetic of shared festivity (Duany, 2017; Negrón-Muntaner, 2017). The Super Bowl, the National Football League (NFL) championship game, functions as one of the largest televised events on the planet. Its cultural dimension exceeds sport: it concentrates extraordinary advertising investment, generates cross-cutting public conversation, and presents itself as a national ceremony in which imaginaries of belonging, consumption and power are negotiated (Kellner, 2003; Couldry, 2003). The halftime show operates as the centrepiece of that ceremony, with its own logic of spectacle, choreography and televisual montage. Its recent history suggests that the show serves as a showcase for cultural legitimation, but also as a terrain of symbolic struggle, where identity, race and nation are articulated under a ritual promise of entertainment (Dayan & Katz, 1992; Van Bauwel, 2021). Within this context, Bad Bunny’s performance on 8 February 2026 acquired a historic character for several converging reasons: it unfolded primarily in Spanish; it mobilised a dense Puerto Rican iconography; it incorporated guests with high media capital; and it delivered an explicit message of love in the face of hate without turning the spectacle into a discursive rally (Associated Press, 2026; Chow, 2026; Lopez, 2026). The primary aim of this article is to analyse and interpret that performance as a political-symbolic discourse mediated by the aesthetics of spectacle. It argues that the show constructs a counter-image of Latin citizenship in the United States through representations of home, labour, celebration and community, and through the re-signification of “America” as a plural continent. The performance replaces a rhetoric of confrontation with a politics of affect, and proposes self-esteem and continental fraternity as a cultural response to a public climate marked by securitised discourses around migration.
Keywords: Televisión y deportes; Televisión - Aspectos sociales; Latinoamericanos - Estados Unidos - Cultura; Televisión; Media events; Industria discográfica; Producción de televisión; Latinidad; Reggaeton